Mapping evidence on postpartum modern family planning service uptake among women in Ethiopia: A scoping review - Cherie, Niguss; Abera, Mulumebet; Tura, Gurmesa (Frontiers in Global Women's Health, 2022)
ABSTRACT Background: In Ethiopia, different fragmented studies were conducted to assess the prevalence and determinants of postpartum contraceptive use. There is discrepancy and inconsistency among reported studies on postpartum modern family planning service. These scoping reviews aimed to collect evidences on postnatal birth control service use and supply a chance to spot key ideas and gaps to research, policy revision, and changes in strategies. Methods: There was different process steps has been done to this scoping review which has analysis questions, distinctive relevant studies, study choice, charting the information and eventually collating, summarizing, and reporting the results. A search was conducted through scientific data bases of PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Hinari and Google scholar. The first outcome of this scoping review was postpartum family planning service use after child birth in Ethiopia. The PRISMA flow diagram was used to select and summarize the selection procedure of the articles. The information of the chosen studies was sorted with the subsequent categories: authors, year of publication, study location, main study objective and method approach employed in information analyses. Results: A total of 1607 records were reclaimed from the database searches and reference list review. PubMed generated 596 articles, CINAHL generated 375 articles, Hinari generated 576 and Google scholar 60 records were identified. A total of 1607 literature's were checked for replication, and 840 records were excluded. The bulk of articles (n =420) were excluded because they did not focus on postpartum family planning service, and 322 articles were excluded due to study setting discrepancy. The follow on 28 full-text articles were read in full using the pre-identified inclusion criteria and included in the scoping review for analysis. Conclusion: From searched and analyzed literature no international controlled trials or longitudinal studies might be known within the search. Early postnatal birth control service uptake with barriers and facilitators was not explored in Ethiopia. There is a definite need for further research to improve early postpartum family planning service use that improves maternal and child health.